Compound Homozygous Rare Mutations in PLCE1 and HPS1 Genes Associated with Autosomal Recessive Retinitis Pigmentosa in Pakistani Families - Masroor Ellahi Babar; Akhtar Ali; Syed Hassan Abbas; Mirza Jawad ul Hasnain; Nida Babar; Hira Babar; Tanveer Hussain; Asif Nadeem; Namra Ayub; Sundus Shahid; Muhammad Tariq Pervez (Iranian Journal of Public Health, 2022)
Background: Retinitis pigmentosa (RP) belongs to pigmentary retinopathies, a generic name for all retinal dystrophies with a major phenotypical and genotypical variation, characterized by progressive reduction of photoreceptor functionality of the rod and cone. Global prevalence of RP is ~ 1/4000 and it can be inherited as autosomal dominant (adRP), autosomal recessive (arRP) or X- linked (xlRP). We designed this study to identify causative mutations in Pakistani families affected with arRP.